Inventory of wildlife and endemic animal trade in Manokwari regency, West Papua - Rumalolas, Nuryanti; Tuhuleruw, Felisita F.; Nebore, Idola Dian Yoku; Tiblola, Zali Natalia (Univeritas Papua, 2025)
This study aims to inventory the trade of wildlife and endemic animals in Manokwari Regency, West Papua, to provide an overview of the economic value and types of animals traded. The method used is a survey method with purposive sampling, based on the presence of respondents who trade animals. Data were then analyzed descriptively from related reports. The results showed that there were 6 species of animals traded in West Manokwari District. The animals come from two classes: aves and mammals. There are four individuals of Mino dumontii, three individuals of Eclectus roratus, two individuals of Cacatua galerita, and two individuals of Lorius lory. While the mammal class has one individual of Spilocuscus maculatus, and one individual of Sus scrofa. Of the six types of animals, there are three species of wildlife including Mino dumontii, Cacatua galerita, and Sus scrofa. While the Papuan endemic animals found consisted of Eclectus roratus, Lorius lory, and Spilocuscus maculatus. This study is expected to assist authorities in identifying actions that need to be taken to reduce the negative impacts of wildlife and endemic trade in Manokwari Regency, West Papua Province.